Finding near-optimal routes for multiple security patrols in a university campus road network - Plaras, James Carlo
Security patrol is an important preventive measure against threat and danger. Since this involves routing, valid and near-optimal routes can be determined using techniques in Graph Theory. This study finds routes for a given number of security patrols in a certain university campus using the Min-Max k-Chinese Postman Problem (MM k-CPP) as the problem model. This problem was solved using simulated annealing (SA) and the results were competitive with other heuristics. The method was implemented with a user friendly interface that would accept Open Street Maps (OSM) data in XML format.
Keywords: Open Street Maps; Routing; Security Patrols; Simulated Annealing